A Gm-C bump equalizer for low-voltage low-power applications - Galembeck, R. (2004)
A low-voltage low-power 2nd-order CMOS pseudo-differential bump-equalizer is presented. Its topology comprises a bandpass section with adjustable center frequency and quality factor, together with a programmable current amplifier. The basic building blocks are triode-operating transconductors, tunable by means of either a DC voltage or a digitally controlled current divider. The bump-equalizer as part of a battery-operated hearing aid device is designed for a 1.4V-supply and a 0.35μm CMOS fabrication process. The circuit performance is supported by a set of simulation results, which indicates a center frequency from 600Hz to 2.4kHz, 1≤Q≤5, and an adjustable gain within ±6dB at center frequency. The filter dynamic range lies around 40dB. Quiescent consumption is kept below 12μW for any configuration of the filter.